Understanding Death Punishment: Historical Perspective, Justification, and Critical Analysis - Utami Yustihasana Untoro; Chrisbiantoro Chrisbiantoro; Hudi Yusuf (Journal of Social Research, 2023)
Debatable of the death penalty based on the issues of justice, humanity, and the prevention of the possibility of crime. The reasons for the rejection of the death penalty are not justified in the view of life as well as humanitarian factors and the imposition of capital punishment will not be capable of preventing crime and reducing crime rates. But for those who agree with the imposition of capital punishment because of the sense of justice and peace that is in the community. The portrait is just a glance at the issues that colored the discourse on the pros and cons of the existence of capital punishment. The retentionist and the abolitionist against the death penalty have an argument based on his theoretical framework and norms. Indonesia as one of the countries with the European Continental legal system still applies the death penalty in the punishment system besides Saudi Arabia with qhisash which is applied in the Islamic Law system. Both countries have a legal standing built on the meta norms, their theories, and philosophies each, of course, has its urgency to be discussed in the middle of countries that condemn the existence of capital punishment. Here's an article that analyzes comparative relations to the applications of the death penalty in both countries that embrace different legal systems, this comparative study will contribute thoughts on the reforms of criminal law in Indonesia.